Brexit: a challenge for the UK constitution, of the UK constitution?. (26th October 2016) - Gordon, Michael
Abstract : The United Kingdom 2016 referendum on membership of the European Union – challenges of pursuing the decision to withdraw – challenges for the UK constitution in commencing, executing, concluding, and legitimising EU withdrawal – domestic constitutional requirements for triggering Article 50 TEU – roles of UK government, UK Parliament, and devolved institutions in Brexit – a second referendum or a national general election on withdrawal terms – exiting the EU as a challenge of the UK's political constitution – Brexit as exposing limitations of the UK's current constitutional arrangements and architecture – Brexit as an unprecedented event and the centrality of politics – constitutional factors contributing to the outcome of the referendum – concerns about sovereignty and the (im)possibility of a national response – potential implications of the referendum for the UK and for the EU